ANALISIS STRATEGI BERSAING PADA UKM LAUNDRY (STUDI KASUS PADA SUPERWASH LAUNDRY KOTA SEMARANG) - Yuniarti, Listia; Hidayat, Wahyu (Jurnal Ilmu Administrasi Bisnis, 2017)
Laundry business is one type of SMEs in the growing home industry today. The demand for laundry business is increasing for workers / employees to students who have busy every day. Laundry service becomes one of the alternatives to save time in doing the job. The high level of demand for laundry services to be one of the drivers of the community to do laundry business. It creates competition, in terms of price or quality. To be able to maintain existence in achieving the purpose of a business unit, then. This study aims to discuss the factors that become strengths, weaknesses, opportunities and quality threats, analysis, and service quality which then determine the formulation of competing strategies that are relevant for laundry service company, especially SuperWash Laundry based on SWOT analysis. This research uses descriptive analysis, with data data technique through interview and observation. Sampling technique using purposive method. Respondents in this research are 15 (fifteen) respondents who are owners and customers of Superwash Laundry business, Semarang. Based on the research results, it can be concluded that SuperWash Laundry in Semarang City performs internal analysis, management, finance, production and development) with no business plan, financial arrangement, job giving, and passive promotion effort. Efforts to improve promotion, promotion, promotion, strategy, and energy. How to work safe. With uncomfortable conditions in the business room. Based on these things. Strategies that Superwash Laundry can apply in the face of competition in accordance with the existing circumstances intensive strategy especially market penetration strategy (market penetration). Market penetration strategy (market penetration) can be applied by SuperWash Laundry through SWOT Matrix by implementing promotion strategy. Promotional strategies can be done by way of operating media campaigns and utilizing internet facilities as a means of promotion, applying rewards to customers to maintain customer loyalty and attract new customers.